Preparation of Pt-based ternary catalyst as cathode material for proton exchange membrane fuel cell by solution route method - S. Thungprasert (2018)
In this research, Pt-based ternary catalysts for proton exchange membrane fuel cell (PEMFC) have been successfully prepared by the solution route method. This type of catalyst was claimed to improve the activities of oxygen reduction reaction (ORR). The ternary catalyst was prepared using 10% platinum, 5% cobalt, and 5% chromium by weight support on untreated and treated carbons by reduction with NaBH4at room temperature. The FTIR spectra showed a new functional group as carboxyl group on treated carbon using H2O2. The XRD patterns for both carbon samples confirmed platinum and carbon phases in the products. The EDS spectra detected platinum, cobalt, chromium, oxygen and carbon atoms in the prepared catalysts. The XAS patterns revealed that the products were mixed Pt-CoO-Cr2O3catalysts. The SEM and TEM images showed more dispersion of catalyst on the treated carbon support surface than on the untreated carbon support. Particles size were 3.97 nm for untreated carbon and 1.93 nm for treated carbon. Finally, the electrochemical property was tested by CV technique. It indicated that Pt-CoO-Cr2O3/C catalyst supported on treated carbon exhibited the highest performance among the prepared ternary alloy catalysts. © 2011 Elsevier B.V. All rights reserved.